The Hidden Burden of Dengue and Chikungunya in Chennai, India. - Isabel Rodríguez-Barraquer; Sunil S Solomon; Periaswamy Kuganantham; Aylur Kailasom Srikrishnan; Canjeevaram K Vasudevan; Syed H Iqbal; Pachamuthu Balakrishnan; Suniti Solomon; Shruti H Mehta; Derek A T Cummings (Public Library of Science (PLoS), 2015)
Dengue and chikungunya are rapidly expanding viruses transmitted by mosquitoes of the genus Aedes. Few epidemiological studies have examined the extent of transmission of these infections in South India despite an increase in the number of reported cases, and a high suitability for transmission.We conducted a household-based seroprevalence survey among 1010 individuals aged 5-40 years living in fifty randomly selected spatial locations in Chennai, Tamil Nadu. Participants were asked to provide a venous blood sample and to complete a brief questionnaire with basic demographic and daily activity information. Previous exposure to dengue and chikungunya was determined using IgG indirect ELISA (Panbio) and IgG ELISA (Novatec), respectively. We used this data to estimate key transmission parameters (force of infection and basic reproductive number) and to explore factors associated with seropositivity. While only 1% of participants reported history of dengue and 20% of chikungunya, we found that 93% (95%CI 89-95%) of participants were seropositive to dengue virus, and 44% (95%CI 37-50%) to chikungunya. Age-specific seroprevalence was consistent with long-tem, endemic circulation of dengue and suggestive of epidemic chikungunya transmission. Seropositivity to dengue and chikungunya were significantly correlated, even after adjusting for individual and household factors. We estimate that 23% of the susceptible population gets infected by dengue each year, corresponding to approximately 228,000 infections. This transmission intensity is significantly higher than that estimated in known hyperendemic settings in Southeast Asia and the Americas.These results provide unprecedented insight into the very high transmission potential of dengue and chikungunya in Chennai and underscore the need for enhanced surveillance and control methods.